Computation of Risk Severity of the Malicious Node using Adaptive Neuro Fuzzy Inference System (ANFIS) - Dharmarajan, R.; Thiagarasu, V. (Asian Journal of Engineering and Applied Technology, 2019)
The Intrusion Detection System (IDS) can be employed broadly for safety network. Intrusion Detection Systems (IDSs) are commonly positioned alongside with other protecting safety mechanisms, such as authentication and access control, as a subsequent line of defence that guards data structures. In this paper, Adaptive Neuro Fuzzy Inference System has utilized to predict the risk severity of the malicious nodes found the previous classification phase.